Satellite assessment of coastal plume variability and its relation to environmental variables in the Sofala Bank - Machaieie, Helder Arlindo; Nehama, Fialho Paloge Juma; Silva, Cleverson Guizan; de Oliveira, Eduardo Negri (Frontiers in Marine Science, 2022)
Monthly composites of remote sensing reflectance at 555 nm wavelength (Rrs555) from Ocean color imagery of MODIS sensor onboard the Aqua platform were used to characterize the spatial and temporal variability of coastal plume in the Sofala Bank and its relation to river discharge, local rainfall, and wind speed. To achieve the objective, maps of monthly composites of Rrs555 over the Sofala Bank were inspected and statistical analysis were performed, including correlation, analysis of variance, and wavelet coherence between environmental variables and both plume area and Rrs555. Climatology of Rrs555 revealed that both plume dispersion and Rrs555 values are higher during June to December and lower during January to May. A positive correlation (r=0.77) between wind speed and monthly time series of Rrs555, and a negative correlation between Zambezi river discharge (r=-0.21) and rainfall (r=-0.67) with Rrs555 were found. These results suggest that variation of suspended matter in the Sofala Bank is mainly controlled by erosion and re-suspension by winds rather than the input of terrigenous matter by the Zambezi River discharge and rainfall, assuming that Rrs555 can be a valid proxy for the inorganic suspended matter. The southern portion of Sofala Bank (i.e., near the mouths of the Pungue and Buzi Rivers) presented higher values of Rrs555 if compared to the central region near the Zambezi river mouth and the northern region near Licungo river mouth. The higher Rrs555 values in the southern region might be associated with higher re-suspension rates due to increased tide mixing, dredging activities, and the shallower nature of bathymetry in the south region. The dominance of wind in controlling the variability of suspended sediments and the eventual relatively more significant contribution of Pungue and Buzi River than the Zambezi in supplying sediments could represent evidence of weakening of Zambezi River's supply of sediments. This process might have started after damming the Zambezi Catchment.